Optimizing agrivoltaic systems for global sustainability: a structural and wind dynamics approach to resilience and performance - Aly, Aly Mousaad (Frontiers in Horticulture, 2026)
This article synthesizes recent research on Agrivoltaics (AV), underscoring its transformative potential to address escalating demands for food and energy while mitigating land-use conflicts and climate change impacts. Key insights reveal that AV systems optimize land productivity, modulate microclimates, and significantly conserve water resources, fostering enhanced agricultural resilience and diversified crop production. Moreover, they deliver substantial economic advantages to farmers, ensuring stable income streams and boosting profitability, while also generating considerable clean energy. The exponential growth in agrivoltaics research reflects its escalating recognition as a multifaceted and vital solution. Despite these compelling benefits, widespread adoption encounters notable challenges. These include overcoming high initial capital costs, optimizing intricate technical configurations to balance light and shade, navigating complex sociopolitical landscapes, and establishing robust waste management and recycling frameworks for PV modules. Crucially, significant structural engineering challenges arise from high-intensity wind loads. Existing codes often misestimate loads, and traditional wind tunnel testing frequently underestimates peak pressures, highlighting a critical lack of comprehensive design standards. Therefore, addressing these challenges demands advanced methodologies—including open-jet testing, sophisticated computational fluid dynamics (CFD) simulations, and a consistent peak load estimation method—to ensure structural resilience and economic viability. Future advancements are critical for unlocking AV’s full potential, necessitating deeper integration of cutting-edge technologies like artificial intelligence and the Internet of Things for dynamic control and predictive analytics. Focused efforts are also required for refining modeling tools, creating comprehensive data repositories, and developing flexible policy instruments. Ultimately, fostering cross-sector collaboration and implementing tailored, holistic approaches will be paramount to building more resilient, sustainable, and economically viable agricultural and energy sectors worldwide.